Respiratory tract infection of fatal severe human bocavirus 1 in a 13-month-old child: A case report and literature review - Liao, Jing; Yang, Zhongying; He, Yu; Wei, Jianhua; Ren, Luo; Liu, Enmei; Zang, Na (Frontiers in Pediatrics, 2022)
Human bocavirus 1 (HBoV1) belongs to the family Parvoviridae and it’s acknowledged that HBoV1 indeed is a respiratory pathogen. We report the case of a 13-month-old boy who presented with cough, shortness of breath, and wheezing, eventually died of severe pneumonia and acute respiratory distress syndrome (ARDS). The mNGS showed that HBoV1 was the only detected pathogen. the nasopharyngeal aspirate (NPA) viral load was 2.08×1010 copies/ml, and the serum viral load was 2.37×105 copies/ml. The child was still oxygen deficient under mechanical ventilation. Chest imaging suggested diffuse bilateral lung lesions, lung injury caused by ARDS. In this case, the clinical symptoms and signs of the child, the high viral load, viremia, and mNGS detection in tracheal aspirate all supported that HBoV1 could cause severe acute respiratory tract infection in children without other pathogen infections.